ANALYSIS OF FACTORS AFFECTING DIVIDEND DISTRIBUTED WITH COMPANY SIZE AS MODERATING VARIABLE - Hastuti, Rini Tri; Octaviani, Dian (International Journal of Application on Economics and Business, 2023)
This study is to examine the effect of Current ratio, free cash flow, DAR (Debt to Total Asset), on dividend distributed with company size as moderation. The research data was obtained directly from published financial reports for the 2018 – 2020 period for the manufacturing industry sector listed on IDX. Sample data was taken by purposive sampling method, namely data with certain criteria that have been selected for research purposes. The data were processed and analyzed using multiple linear regression with the application of the SPSS 25 statistical program. The results of the processed data test showed that dividend distributed was negatively affected by free cash flow and significant, dividend distributed was negatively and not significantly affected by DAR (Debt to Total Asset), while Current ratio had no positive effect. significant effect on dividend distributed. The moderating variable of company size shows the results of the test that company size cannot moderate the effect of free cash flow, DAR (Debt to Total Asset), and Current ratio on dividend distributed.